2022
DOI: 10.1017/s0022029922000243
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiae-induced autophagy of bovine mammary epithelial cell via PI3K/AKT/mTOR pathway

Abstract: Streptococcus agalactiae (S. agalactiae) infection is a significant cause of mastitis, resulting in loss of cellular homeostasis and tissue damage. Autophagy plays an essential function in cell survival, defense, and the preservation of cellular homeostasis, and is often part of the response to pathogenic challenge. However, the effect of autophagy induced by S. agalactiae in bovine mammary epithelial cells (bMECs) is mainly unknown. So in this study, an intracellular S. agalactiae infection model was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…S. dysgalactiae can not only form biofilm but also invade and survive within mammary epithelial cells, and persist for long periods, which can avoid the bactericidal action of antibiotics, resulting in persistent infection ( Calvinho and Oliver, 1998 ). Streptococcus also can induce autophagy to increase inflammatory reactions of bovine mammary epithelial cells ( Chen et al, 2022 ; Qi et al, 2022 ). Because of the low intracellular accumulation and special intracellular environmental effects, it is difficult for the antibiotics to play a good bactericidal effect in intracellular.…”
Section: Discussionmentioning
confidence: 99%
“…S. dysgalactiae can not only form biofilm but also invade and survive within mammary epithelial cells, and persist for long periods, which can avoid the bactericidal action of antibiotics, resulting in persistent infection ( Calvinho and Oliver, 1998 ). Streptococcus also can induce autophagy to increase inflammatory reactions of bovine mammary epithelial cells ( Chen et al, 2022 ; Qi et al, 2022 ). Because of the low intracellular accumulation and special intracellular environmental effects, it is difficult for the antibiotics to play a good bactericidal effect in intracellular.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary studies did not confirm that miR-383 is upregulated in mastitic milk; therefore, this molecule was excluded from the experiment. However, other studies found that miR-383 was significantly upregulated in CMT-positive milk ( 18 ) and in mammary epithelial cells in Streptococcus agalactiae -induced mastitis ( 26 ).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, autophagy also plays a role in the development of mastitis. Evidence suggests that pathogens, such as Streptococcus agalactiae, induce autophagy through the PI3K/ATK/mTOR pathway in bovine mammary epithelial cells (BMECs) [37], and Streptococcus lutetiensis induces autophagy through oxidative stress in BMECs [38]. Additionally, taurine inhibits the inflammatory response induced by Streptococcus uberis by regulating autophagy in MAC-T cells [39].…”
Section: Discussionmentioning
confidence: 99%